The Alternate Arm Converter (AAC) - "short-overlap" mode operation - analysis and design parameter selection - Farr, Ewan; Feldman, Ralph; Clare, Jon C.; Watson, Alan James; Wheeler, Patrick (IEEE, 2018)
This paper presents converter operation principles and theoretical analyses for “short-overlap” mode operation of the Alternate Arm Converter (AAC), which is a type of modular multilevel Voltage Source Converter (VSC) that has been proposed for HVDC transmission applications. Fourier series expressions for the ideal arm current and reference voltage are derived, for the first time, in order to develop an expression for the sub-module capacitance required to give a selected peak-peak voltage ripple of the summed sub-module capacitor voltages in an arm. The DC converter current contains non-negligible low order even harmonics; this is verified by deriving, for the first time, a Fourier series expression for this current. As the DC converter current needs to be filtered to form a smooth DC grid current, a novel DC filter arrangement is proposed, which uses the characteristics of a simplified DC cable model, as well as the capacitance of the DC link and additional DC link damping resistance, in order to form a passive low pass filter. Results obtained from a simulation model, which is based on an industrial HVDC demonstrator, are used in order to verify the presented converter operation principles and theoretical analyses.